Diversity in old age: Stereotyping of subgroups of older people across cultures - Vauclair, Christin‐Melanie; Esteves, Carla Sofia; Eyssel, Friederike; Harb, Charles (Asian journal of social psychology, 2024)
An ageing population is increasingly recognised as a critical concern in the social sciences, especially in regard to the issue of ageism. The literature suggests that older people are subject to ambivalent and paternalistic judgements. However, this does not consider diversity within the older population and that cultures may differ in how they perceive and evaluate diverse groups of older people. To address these gaps, a pre‐study was conducted employing a freelisting task to identify old age subgroups. In the main study, participants from the United States and Germany (individualistic‐loose cultures) and Japan, Lebanon and Portugal (collectivistic‐tight cultures) were asked to evaluate 19 distinct subgroups of older people by using stereotype content measures. The results suggest that subgroups' clusters were generally perceived as low, medium, or high on both the competence and warmth dimensions providing no support for clearly ambivalent old age subgroup stereotypes. As expected, competence and warmth were consistently associated with the socio‐structural variables perceived status and threat. Overall, the results point to similar patterns across cultures with different subgroups being evaluated in a similar fashion on stereotype content measures. This highlights the importance of promoting a more nuanced understanding of older people when addressing ageism in different cultures.